Computational Experience with Modified Coefficients Conjugate Gradient for Image Restoration (European Journal of Pure and Applied Mathematics, 2023)
The Conjugate Gradient Method is a numerical optimization technique that finds the optimal solution by focusing on the coefficient conjugate. This paper presents a new coefficients conjugate gradient method for removing impulse noise from images, which is based on a quadratic function and is proven to be globally convergent. Results show that it is an effective method for image restoration.
Keywords: Conjugate gradient method; Coefficient conjugate gradient; Image restoration